Heat-resistant stable alkali-free boroaluminosilicate glass with high crystallization margin and preparation method of alkali-free boroaluminosilicate glass

By adjusting the composition of alkali-free boron aluminosilicate glass and using overflow pull-down method to mold, the problem that existing glass cannot take into account both heat stability and devitrification resistance, and high strain point and liquid viscosity are achieved The increase in crystallization margin extends the production line life and reduces production costs.

CN119461844APending Publication Date: 2025-02-18IRICO DISPLAY DEVICES CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411374783.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing alkali-free boron aluminosilicate glasses cannot take into account both high heat resistance and devitrification resistance.

Method used

By adjusting the composition of the glass, ensure that the mole percentage of SiO2 is between 68.54 and 72.82%, the mole percentage of Al2O3 is between 11.84 and 13.5%, the mole percentage of B2O3 is≤2.23%, the mole percentage of MgO is between 4.72 and 6.6%, and the mole percentage of CaO is between 11.84 and 13.5%, the mole percentage of B2O3 is between 2.23%, the mole percentage of MgO is between 4.72 and 6.6%, and the mole percentage of CaO is between 11.84 and 13.5%, the mole percentage of B2O3 is between 11.84 and 13.5%, the mole percentage of B2O3 is between 2.23%, the mole percentage of MgO is between 4.72 and 6.6%, and the mole percentage of CaO is between 11.84 and 13.5%, The molar percentage of SrO was between 4.65 and 5.8%, the molar percentage of SrO was between 0.8 and 1.5%, the molar percentage of BaO was between 3.2 and 3.79%, and the molar percentage of SnO2 was 0.1%, and the molar percentage of SnO2 was 0.1%. The overflow pull-down method was used for molding.

Benefits of technology

Achieved high strain point, liquid-phase viscosity and crystallization margin of alkali-free boron aluminosilicate glass, reducing crystallization defect rate, extending production line life, reducing production costs, and taking into account high heat resistance and stability and resistance to devitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of electronic glass, in particular to heat-resistant stable alkali-free boroaluminosilicate glass with high crystallization margin and a preparation method of the alkali-free boroaluminosilicate glass. The alkali-free boroaluminosilicate glass with heat resistance, stability and high crystallization margin is prepared from the following raw materials in percentage by mole: 68.54 to 72.82 percent of SiO2, 11.84 to 13.5 percent of Al2O3, less than or equal to 2.23 percent of B2O3, 4.72 to 6.6 percent of MgO, 4.65 to 5.8 percent of CaO, 0.8 to 1.5 percent of SrO, 3.2 to 3.79 percent of BaO and 0.1 percent of SnO2, the ratio of SiO2 to Al2O3 is 81.63 to 84.66 percent, and the ratio of (MgO + CaO + SrO + BaO) to Al2O3 is 1.15 to 1.30. The alkali-free boroaluminosilicate glass obtained in the invention has a high strain point and crystallization margin, and also has high heat-resistant stability and devitrification resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic glass, and in particular to heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass and a preparation method thereof. Background Art

[0002] With the continuous development of display technology, people's demand for display devices is gradually tending towards large-size, high-resolution and high-definition screens. Compared with amorphous silicon thin-film transistor displays, polycrystalline silicon thin-film transistors can transmit electrons faster and more efficiently, and have higher electron mobility, so polycrystalline silicon can make smaller and faster transistors, and ultimately produce brighter and faster displays. But for polycrystalline silicon transistors, during their processing, the substrate is heated to 450~600℃, which is a higher processing temperature than the 350℃ peak temperature used to make amorphous silicon transistors. At such temperatures, the substrate glass is very easy to deform. In response to this situation, the heat resistance stability of the substrate glass can be improved by adjusting the substrate glass components, the molding process and other processes. This is mainly because high heat-resistant and stable glass (high strain point) can prevent deformation caused by poor heat resistance of the glass during the heat treatment process during panel production.

[0003] At the same time, the entire production process of polysilicon substrate glass needs to be carried out at a higher temperature. The production process temperature of substrate glass is high. During the melting process, the substances in the furnace are more likely to corrode the refractory materials in the production line, resulting in more stone defects inside the glass, and the high molding temperature will cause the overflow bricks to creep more, seriously affecting the life of the production line and increasing production costs. At the same time, the liquidus temperature of the substrate glass is related to the molding production of the substrate glass and the product quality of the substrate glass. Only by controlling the liquidus temperature of the substrate glass below a certain temperature and expanding the difference between the molding temperature and the liquidus temperature (crystallization margin) can the normal molding production be guaranteed. The liquidus temperature of the substrate glass is related to factors such as glass composition, glass structure and glass phase separation. By testing the production process and liquidus temperature of different material squares, the material square can be selected or optimized. Therefore, accurately testing the melting temperature, molding temperature and liquidus temperature of different material squares of substrate glass has certain practical significance for the formulation of liquid crystal substrate glass production process, the stability of molding process and the control of product quality.

[0004] The currently disclosed substrate glass has a high crystallization margin and liquidus viscosity, which significantly reduces the risk of devitrification of the substrate glass in the cold section of the molding equipment. However, the heat stability and devitrification resistance of the substrate glass are still insufficient, and it is impossible to simultaneously take into account high heat stability and devitrification resistance. Summary of the invention

[0005] The object of the present invention is to provide a heat-resistant, stable, and high-devitrification-margin alkali-free boroaluminosilicate glass, so as to solve the problem that the alkali-free boroaluminosilicate glass in the prior art cannot have both high heat resistance stability and devitrification resistance.

[0006] The present invention also provides a method for preparing heat-resistant, stable and high-crystallization-margin alkali-free boroaluminosilicate glass to solve the problem in the prior art that the alkali-free boroaluminosilicate glass cannot have both high heat resistance stability and devitrification resistance.

[0007] In order to solve the above problems, the present invention proposes a heat-resistant, stable, high-crystallization margin alkali-free boroaluminosilicate glass, and the technical solution adopted is: A heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass, whose raw materials include, by mole percentage, 68.54-72.82% SiO2, 11.84-13.5% Al2O3, ≤2.23% B2O3, 4.72-6.6% MgO, 4.65-5.8% CaO, 0.8-1.5% SrO, 3.2-3.79% BaO and 0.1% SnO2, wherein SiO2+Al2O3 is 81.63-84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15-1.30.

[0008] The beneficial effects of the present invention are as follows: SiO2 is a network former in glass, and the molar percentage of SiO2 is designed to be 68.54-72.82%, which is beneficial to reducing the thermal expansion coefficient of alkali-free boroaluminosilicate glass and improving the thermal stability, chemical stability, softening point, strain point, heat resistance, hardness, mechanical strength and other properties of alkali-free boroaluminosilicate glass; the molar percentage of Al2O3 is designed to be 11.84-13.5%, which is used to increase the stability of alkali-free boroaluminosilicate glass, reduce the thermal expansion coefficient and increase the hardness of glass; the molar percentage of B2O3 is designed to be ≤2.23%, which is used to increase the viscosity of alkali-free boroaluminosilicate glass and reduce the liquidus temperature; the molar percentage of MgO is designed to be 4.72-6.6%, which is used to reduce the high-temperature viscosity of alkali-free boroaluminosilicate glass and improve the melting performance of alkali-free boroaluminosilicate glass; the molar percentage of CaO is designed to be 4.65-5. .8% is also used to reduce the high-temperature viscosity of alkali-free boroaluminosilicate glass and significantly improve the solubility of alkali-free boroaluminosilicate glass; the molar percentage of SrO is designed to be 0.8~1.5% to suppress the increase in the liquidus temperature of alkali-free boroaluminosilicate glass; the molar percentage of BaO is designed to be 3.2~3.79%, which is beneficial to reducing the liquidus temperature of alkali-free boroaluminosilicate glass; the molar percentage of SnO2 as a clarifier is designed to be 0.1%, which can promote the elimination or dissolution and absorption of bubbles in the molten liquid of alkali-free boroaluminosilicate glass; among them, the molar percentage of SiO2+Al2O3 is designed to be 81.63~84.66%, which is beneficial to increase the strain point of alkali-free boroaluminosilicate glass; (MgO+CaO+SrO+BaO) / Al2O3 is designed to be 1.15~1.30, so that the alkali-free boroaluminosilicate glass can take into account both high specific modulus and high strain point, thereby improving the resistance to devitrification.

[0009] The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass provided by the present invention improves the strain point of the alkali-free boroaluminosilicate glass and reduces its deformation during panel processing and manufacturing by controlling the composition and molar percentage; at the same time, the crystallization margin of the alkali-free boroaluminosilicate glass in the overflow molding and down-drawing process is improved, the crystallization defect rate is reduced, the life of the production line is extended, and the production cost of the glass is reduced. The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass has both high heat stability and resistance to devitrification.

[0010] In order to further improve the strain point, liquidus viscosity and crystallization margin of the glass, preferably, in terms of molar percentage, the raw materials include: 69.12~72.82% SiO2, 11.84~13.1% Al2O3, ≤2.23% B2O3, 5.28~6.59% MgO, 4.65~5.78% CaO, 0.8~1.5% SrO, 3.2~3.79% BaO and 0.1% SnO2, wherein SiO2+Al2O3 is 81.63~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.30.

[0011] In order to further improve the strain point, liquidus viscosity and crystallization margin of the glass, preferably, in terms of molar percentage, the raw materials include: 69.33~72.82% SiO2, 11.84~13.1% Al2O3, ≤2.23% B2O3, 5.28~6.59% MgO, 4.65~5.52% CaO, 0.8~1.5% SrO, 3.2~3.79% BaO and 0.1% SnO2, wherein SiO2+Al2O3 is 81.63~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.30.

[0012] In order to further improve the strain point, liquidus viscosity and crystallization margin of the glass, preferably, in terms of molar percentage, the raw materials include: 70.5~72.82% SiO2, 11.84~13.1% Al2O3, ≤1.23% B2O3, 5.28~6.29% MgO, 4.99~5.01% CaO, 0.8~1.1% SrO, 3.54~3.79% BaO and 0.1% SnO2, wherein SiO2+Al2O3 is 83~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.29.

[0013] In order to obtain the highest strain point, liquidus viscosity and crystallization margin of the glass, preferably, in terms of molar percentage, the raw materials include: 72.82% SiO2, 11.84% Al2O3, 0% B2O3, 5.28% MgO, 5.32% CaO, 1.1% SrO, 3.54% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.29.

[0014] In order to make the glass have high heat resistance stability during processing, preferably, the strain point temperature of the heat-resistant stable high crystallization margin alkali-free boroaluminosilicate glass is above 735° C. The strain point temperature is higher than 735° C. The glass with a high strain point can suppress the thermal deformation of the glass plate in the manufacture of polysilicon transistor displays, thereby improving the yield rate of display manufacturing.

[0015] In order to make the glass have high resistance to devitrification in the overflow down-drawing process, preferably, the liquidus viscosity of the heat-resistant stable high crystallization margin alkali-free boroaluminosilicate glass is 203426P or more, and the crystallization margin is 80°C or more. The liquidus viscosity is greater than 200,000 poise, the forming performance is excellent, and the glass sheet can be easily formed by the overflow down-drawing method, which can improve the surface quality of the glass sheet and reduce the manufacturing cost of the glass sheet.

[0016] Preferably, the strain point temperature of the alkali-free boroaluminosilicate glass is 736-754.1°C, the liquidus viscosity is 211706.6-357812P, and the crystallization margin is 81.1-107.1°C.

[0017] Preferably, the strain point temperature of the alkali-free boroaluminosilicate glass is 736-754.1°C, the liquidus viscosity is 226700-357812P, and the crystallization margin is 87.1-107.1°C.

[0018] Preferably, the strain point temperature of the alkali-free boroaluminosilicate glass is 743.2-754.1°C, the liquidus viscosity is 226700-357812 P, and the crystallization margin is 92.8-107.1°C.

[0019] Preferably, the strain point temperature of the alkali-free boroaluminosilicate glass is 754.1°C, the liquidus viscosity is 357812P, and the crystallization margin is 107.1°C.

[0020] The present invention also proposes a method for preparing a heat-resistant, stable, high-crystallization margin alkali-free boroaluminosilicate glass, the technical solution adopted is: A method for preparing heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass comprises the following steps: sequentially mixing, melting, and clarifying the raw materials to obtain a clarified glass melt; and then forming the clarified glass melt by an overflow down-draw method to obtain the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass.

[0021] The beneficial effects of the present invention are as follows: the molding process of the preparation method is stable during the preparation process, the quality of the prepared alkali boroaluminosilicate glass product is controlled, and it has a high strain point. The preparation method is safe, easy to operate and low in cost.

[0022] In order to make the glass melt thoroughly and evenly, preferably, the melting temperature is 1590-1630°C.

[0023] In order to make the glass melt uniformly molded and to achieve high product quality, preferably, the molding temperature is 1270-1300°C. DETAILED DESCRIPTION

[0024] In the prior art, alkali-free boron aluminosilicate glass cannot simultaneously take into account high heat resistance stability and devitrification resistance. The present invention provides an alkali-free boron aluminosilicate glass with heat resistance stability and high crystallization margin, wherein the raw materials include, by mole percentage, 68.54-72.82% SiO2, 11.84-13.5% Al2O3, ≤2.23% B2O3, 4.72-6.6% MgO, 4.65-5.8% CaO, 0.8-1.5% SrO, 3.2-3.79% BaO and 0.1% SnO2, wherein SiO2+Al2O3 is 81.63-84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15-1.30.

[0025] The technical concept of the present invention is: in the heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass, SiO2 is a network former in the glass, which forms an irregular continuous network with the structure of silicon-oxygen tetrahedron [SiO4], constituting a glass skeleton, and can reduce the thermal expansion coefficient of the glass, and improve the thermal stability, chemical stability, softening point, strain point, heat resistance, hardness, mechanical strength and other properties of the glass. If its molar percentage is lower than 68.54%, it is difficult to increase the strain point, and the density will also become too high. If the molar percentage is higher than 72.82%, in addition to the increase in high-temperature viscosity and the decrease in solubility, it is more likely to cause devitrification crystallization, which increases the liquidus temperature. Therefore, in the present invention, the molar percentage of SiO2 is 68.54~72.82%.

[0026] Al2O3 is a network-forming oxide. When there are insufficient oxygen atoms in the glass, the coordination state of aluminum is aluminum oxide octahedron [AlO6], which is in the network gap; when there are excess oxygen atoms in the glass, the coordination state of aluminum is aluminum oxide tetrahedron [AlO4], which enters the glass structure and plays a role in filling the network, increasing the stability of the glass, reducing the thermal expansion coefficient, and increasing the hardness of the glass. Increasing its molar percentage can increase the strain point temperature and elastic modulus of the glass, but if the molar percentage is higher than 13.5%, devitrified crystals such as mullite and calcium feldspar are easily precipitated, which increases the liquidus temperature. Therefore, in the present invention, the molar percentage of Al2O3 is 11.84~13.5%.

[0027] B2O3 in glass can mainly reduce the viscosity of glass at high temperature and play a role in fluxing, while it can increase the viscosity of glass and reduce the liquidus temperature at low temperature. However, too much B2O3 will increase the expansion coefficient of glass, reduce the strain point temperature and elastic modulus. Therefore, its molar percentage is ≤2.23%. If the molar percentage is higher than 2.23%, the strain point of the glass will drop significantly, resulting in large thermal deformation during display processing. Therefore, in the present invention, the molar percentage of B2O3 is ≤2.23%.

[0028] MgO is used to reduce high temperature viscosity and improve the melting performance of glass. If the MgO content is too high, the strain point will drop significantly and the liquidus temperature will increase, which will deteriorate the resistance to devitrification and be unfavorable for the molding process of the overflow down-draw method. Therefore, in the present invention, the molar percentage of MgO is 4.72~6.6%.

[0029] CaO is a component that reduces high temperature viscosity and significantly improves solubility without lowering the strain point. However, if the CaO content is too high, the glass is prone to devitrification and the thermal expansion coefficient becomes too high. Therefore, in the present invention, the molar percentage of CaO is 4.65-5.8%.

[0030] SrO, like CaO, is a component that reduces high-temperature viscosity and significantly improves solubility without lowering the strain point. At the same time, SrO is also a component that inhibits phase separation and improves devitrification resistance, and is therefore also a component that inhibits the rise in liquidus temperature. If the SrO content is too low, it is difficult to inhibit phase separation and thus improve devitrification resistance, but if the content is too high, strontium silicate series devitrification crystals are likely to occur, reducing devitrification resistance. Therefore, in the present invention, the molar percentage of SrO is 0.8 to 1.5%.

[0031] Compared with SrO, BaO is a component that significantly improves the resistance to devitrification. It is beneficial to reduce the liquidus temperature of glass. However, if BaO replaces other alkaline earth metal oxides or the BaO content is too high, the melting temperature will increase, the high-temperature viscosity will increase, and the melting performance will decrease. At the same time, as a divalent network exometallic oxide, BaO has a relatively serious erosion on refractory materials. Based on the environmental protection and lightweight development trend of substrate glass, the addition amount of BaO must be controlled. Therefore, in the present invention, the molar percentage of BaO is 3.2-3.79%.

[0032] SnO2 is added to the basic glass components as a clarifier, which can promote the elimination of bubbles or dissolution and absorption in the glass melt. The molar percentage of SnO2 is designed to be 0.1%, which can promote the elimination of bubbles or dissolution and absorption in the glass melt.

[0033] Among them, SiO2 and Al2O3 are both network-forming oxides, and both have the effect of increasing the strain point. However, when the SiO2 content increases, it is easy to precipitate devitrified crystals such as cristobalite; when the Al2O3 content is too high, it is easy to precipitate devitrified crystals of alkaline earth metal aluminum silicate such as mullite and anorthite. Therefore, the molar percentage of SiO2+Al2O3 in this application is 81.63~84.66%.

[0034] RO represents alkaline earth metal oxides, and the present invention includes MgO, CaO, SrO, and BaO. The ratio of the sum of the molar amounts of alkaline earth metal oxides (MgO+CaO+SrO+BaO) to the molar amount of Al2O3 is designed to form new compounds with silicates in the glass, thereby lowering the melting point of the glass and improving the chemical stability of the glass. This ratio takes into account both high specific modulus and high strain point, thereby improving the resistance to devitrification. However, if the ratio is too small, devitrification crystallization is easily caused by alkaline earths, and if the ratio is too large, devitrification crystallization of alkaline earth aluminosilicates such as calcium feldspar is easily caused. Therefore, in the present application, (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.30, so that the glass has high heat resistance stability, a large crystallization margin (the difference between the molding temperature and the liquidus temperature), and a higher liquidus viscosity, which is conducive to the stability of the overflow down-draw molding process.

[0035] The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass provided by the present invention increases the strain point of the alkali-free boroaluminosilicate glass and reduces its deformation during panel processing and manufacturing by controlling the composition and molar percentage; at the same time, the crystallization margin of the alkali-free boroaluminosilicate glass in the overflow molding down-drawing process is increased, the crystallization defect rate is reduced, the life of the production line is extended, and the production cost of the glass is reduced. The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass of the present application has a strain point temperature of 735.2°C or more, a liquidus viscosity of 203426.2P or more, and a crystallization margin of 80.2°C or more.

[0036] Specifically, the preparation method of heat-resistant, stable and high-crystallization margin alkali-free boroaluminosilicate glass comprises the following steps: (1) Calculate the molar percentage content of each raw material and weigh the raw materials corresponding to each component, pour the raw materials of each component into a mixer, and mix them evenly to obtain a mixed material; (2) The mixed material is put into a glass furnace, heated and melted in the glass furnace to form a glass melt, and then the glass melt flows into a platinum channel for clarification to obtain a clarified glass melt; (3) The clarified glass melt is formed into sheet glass by an overflow down-draw process, which is a heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass.

[0037] Preferably, in step (2), the melting temperature is 1590-1630°C.

[0038] Preferably, in step (3), the molding temperature is 1270-1300° C., which is the temperature in the overflow down-draw molding process during the glass preparation process.

[0039] The implementation process of the present invention is described in detail below in conjunction with specific embodiments.

[0040] In the following examples and comparative examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.

[0041] 1. Embodiment of the method for preparing the heat-resistant, stable and high crystallization margin alkali-free boroaluminosilicate glass of the present invention Examples 1-20 Embodiments 1-20 all provide heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass; wherein the preparation method of the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass comprises the following steps: (1) According to the proportions of each component in Table 1 and Table 2, calculate and weigh the raw materials corresponding to each component, pour the raw materials of each component into a mixer, and mix them evenly to obtain a mixed material; (2) putting the mixed material into a glass furnace, heating and melting it in the glass furnace to form a glass melt, and then flowing the glass melt into a platinum channel for clarification to obtain a clarified glass melt, wherein the melting temperature is 1600° C.; (3) The clarified glass melt is molded into sheet glass by an overflow down-draw molding process, namely, heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass, wherein the molding temperature is 1280°C.

[0042] In the present application, when the melting temperature is 1590° C. or 1630° C., the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass prepared thereby achieves the same technical effects as those of the above-mentioned embodiments.

[0043] In the present application, when the molding temperature is 1270° C. or 1300° C., the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass prepared thereby achieves the same technical effects as those of the above-mentioned embodiments.

[0044] Table 1 Alkali-free boroaluminosilicate glass composition ratios in Examples 1-10

[0045] Table 2 Distribution ratio of each group of alkali-free boroaluminosilicate glass in Examples 11-20

[0046] 2. Experimental Examples The strain point temperature, forming temperature, liquidus temperature, liquidus viscosity and crystallization margin of the heat-resistant, stable and high-crystallization-margin alkali-free boroaluminosilicate glass prepared in Examples 1-20 were tested and calculated. Specifically, the strain point temperature was measured by the standard method of ASTM C336, and the glass was drawn into glass fibers as required by the standard, and the strain point temperature was detected in a dedicated device; for the liquidus viscosity, the viscosity-temperature curve of the glass was first tested. The viscosity-temperature curve test was performed according to the standard method of ASTM C-965. The sheet glass prepared in Examples 1-20 was crushed and the glass particles of 10 to 30 mesh screened with a sieve were placed in a corresponding container, the temperature was raised to melt the glass into glass liquid, and then the rotor was lowered. The rotor rotated at different speeds, and the torque at different speeds was read by the corresponding software, thereby calculating the viscosity of the molten glass at different temperatures. The corresponding liquidus viscosity is then calculated based on the viscosity-temperature curve obtained from the viscosity test; the molding temperature is the temperature corresponding to the corresponding viscosity on the viscosity-temperature curve obtained above; the liquidus temperature is obtained by crushing the sheet glass prepared in Example 1-20 and placing the 10-30 mesh glass particles sieved by the sieve into a long strip container, and placing it in a furnace with a temperature gradient and keeping it warm at a certain temperature, taking it out after keeping warm for 24 hours, observing the corresponding position of the initial crystallization under a microscope after cooling, and calculating the corresponding temperature value to obtain the liquidus temperature; the crystallization margin is the difference between the molding temperature and the liquidus temperature. The specific test results are shown in Tables 3 and 4: Table 3 Performance test results of alkali-free boroaluminosilicate glass prepared in Examples 1-10

[0047] Table 4 Performance test results of alkali-free boroaluminosilicate glass prepared in Examples 11-20

[0048] It can be seen from Tables 3 and 4 that the strain point temperature of the heat-resistant, stable, high crystallization margin alkali-free boroaluminosilicate glass of the present application is above 735.2°C, and can reach up to 754.1°C, the liquidus viscosity is above 203426.2P, and can reach up to 357812P, and the crystallization margin is above 80.2°C, and can reach up to 107.1°C. In Example 6, the strain point temperature, liquidus viscosity, and crystallization margin of the heat-resistant, stable, high crystallization margin alkali-free boroaluminosilicate glass are the highest. This shows that the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass provided by the present application controls the molar percentage range of each raw material so that the alkali-free boroaluminosilicate glass has a high strain point, reduces its deformation during the panel processing and manufacturing process, and improves its heat resistance temperature; at the same time, the crystallization margin and liquidus viscosity of the alkali-free boroaluminosilicate glass in the overflow molding and down-drawing process are improved, the crystallization defect rate is reduced, its resistance to devitrification is improved, the life of the production line is extended, and the production cost of the glass is reduced. The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass of the present application takes into account both high heat stability and resistance to devitrification.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass, characterized in that: In terms of molar percentage, the raw materials include: 68.54~72.82% SiO2, 11.84~13.5% Al2O3, ≤2.23% B2O3, 4.72~6.6% MgO, 4.65~5.8% CaO, 0.8~1.5% SrO, 3.2~3.79% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 81.63~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.

30.

2. The heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass according to claim 1, characterized in that: In terms of molar percentage, the raw materials include: 69.12~72.82% SiO2, 11.84~13.1% Al2O3, ≤2.23% B2O3, 5.28~6.59% MgO, 4.65~5.78% CaO, 0.8~1.5% SrO, 3.2~3.79% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 81.63~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.

30.

3. The heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass according to claim 1, characterized in that: In terms of molar percentage, the raw materials include: 69.33~72.82% SiO2, 11.84~13.1% Al2O3, ≤2.23% B2O3, 5.28~6.59% MgO, 4.65~5.52% CaO, 0.8~1.5% SrO, 3.2~3.79% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 81.63~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.

30.

4. The heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass according to claim 1, characterized in that: In terms of molar percentage, the raw materials include: 70.5~72.82% SiO2, 11.84~13.1% Al2O3, ≤1.23% B2O3, 5.28~6.29% MgO, 4.99~5.01% CaO, 0.8~1.1% SrO, 3.54~3.79% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 83~84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.15~1.

29.

5. The heat-resistant, stable, high-crystallization-margin alkali-free boroaluminosilicate glass according to claim 1, characterized in that: In terms of molar percentage, the raw materials include: 72.82% SiO2, 11.84% Al2O3, 0% B2O3, 5.28% MgO, 5.32% CaO, 1.1% SrO, 3.54% BaO and 0.1% SnO2, among which SiO2+Al2O3 is 84.66%, and (MgO+CaO+SrO+BaO) / Al2O3 is 1.

29.

6. The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass according to any one of claims 1 to 5, characterized in that: The strain point temperature of the heat-resistant, stable, and high-devitrification-margin alkali-free boroaluminosilicate glass is 735° C. or higher.

7. The heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass according to any one of claims 1 to 5, characterized in that: The liquidus viscosity of the heat-resistant, stable, and high-crystallization-margin alkali-free boroaluminosilicate glass is greater than 203426P, and the crystallization margin is greater than 80°C.

8. A method for preparing heat-resistant, stable and high-crystallization margin alkali-free boroaluminosilicate glass, characterized in that: The method comprises the following steps: according to the raw materials of the heat-resistant, stable and high-crystallization-margin alkali-free boroaluminosilicate glass according to any one of claims 1 to 7, the raw materials are sequentially mixed, melted and clarified to obtain a clarified glass melt, and then the clarified glass melt is formed by an overflow down-draw method to obtain the heat-resistant, stable and high-crystallization-margin alkali-free boroaluminosilicate glass.

9. The method for preparing heat-resistant, stable and high-crystallization margin alkali-free boroaluminosilicate glass according to claim 8, characterized in that: The melting temperature is 1590-1630°C.

10. The method for preparing heat-resistant, stable and high-crystallization margin alkali-free boroaluminosilicate glass according to claim 8, characterized in that: The molding temperature is 1270-1300°C.

Citation Information

Cited By

  • Alkali-free boroaluminosilicate glass having good thermal stability and high crystallization margin, and preparation method therefor

    WO2026066652A1